THE EFFECT OF CAPITAL STRUCTURE, LIQUIDITY AND PROFITABILITY ON COMPANY VALUE IN THE FOOD SUB SECTOR AND BEVERAGES ON THE INDONESIA STOCK EXCHANGE - Ni Wayan Rudini; Gusti Ayu Mahanavami; Nyoman Parta; Ni Nyoman Menuh (Bajang Institute, 2021)
This research is motivated by the inconsistency of the results of previous studies so that the purpose of this study is to determine the effect of capital structure, liquidity and profitability on firm value in the Food and Beverage Sub-Sector on the Indonesia Stock Exchange in 2016-2019. The population in this study is the Food and Beverage Sub-Sector companies on the Indonesia Stock Exchange in 2016-2019 through the website www.idx.co.id, where the sample used is 12 companies with 48 observations and the analytical technique used is the classical assumption test, multiple linear regression, and t test. The results of the analysis show that the capital structure has a negative effect on firm value in the food and beverage sub-sector companies on the Indonesia Stock Exchange. Liquidity has a negative effect on firm value in food and beverage sub-sector companies on the Indonesia Stock Exchange. Profitability has a positive effect on firm value in food and beverage sub-sector companies on the Indonesia Stock Exchange. .